Invasion of metastatic human follicular thyroid cancer is inhibited via antagonism of protein kinase C - Hölting, Thomas; Duh, Quan-Yang; Clark, Orlo H.; Herfarth, Christian (Cancer letters, 1997)
Signal transduction of a human follicular thyroid cancer cell line (FTC133) was investigated. The protein kinase C (PKC)-agonist TPA enhanced invasion by 15%, whereas its antagonists staurosporine, chelerythrine and calphostin C were inhibiting by up to 62%. TSH and EGF stimulated invasion of FTC133. Antagonism of PKC reversed TSH-mediated stimulation, whereas it had no effect on EGF-stimulation. Our data provide evidence for an essential role of PKC in signal transduction of invasive thyroid cancer.
Elektronische Reproduktion der Druck-Ausgabe 5. Januar 1998
Gesehen am 26.08.2025